2018
DOI: 10.1108/jfc-05-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Helping auditors identify deception through psycholinguistics

Abstract: Purpose-This paper reviews an array of psycholinguistic techniques that auditors can deploy to explore written and oral language for signs of deception. The review is drawn upon to propose some elements of a forward research agenda. Design/Methodology/Approach-Relevant literature across several disciplines is identified through key word searches of major bibliographic databases. Findings-The techniques highlighted have considerable potential for use by auditors to identify audit contexts which merit closer aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…But, what makes a good fraud investigator? There are studies that explore techniques that may be utilized by auditors in detecting fraud, such as linguistic analysis techniques which “help detect deception within written and oral financial communications” (Nicolaides et al , 2018). However, this study posits that the auditor’s personality may be as important as the techniques applied.…”
Section: Introductionmentioning
confidence: 99%
“…But, what makes a good fraud investigator? There are studies that explore techniques that may be utilized by auditors in detecting fraud, such as linguistic analysis techniques which “help detect deception within written and oral financial communications” (Nicolaides et al , 2018). However, this study posits that the auditor’s personality may be as important as the techniques applied.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet has facilitated the activities of 419ers because it offers a wider geographical coverage, access to a large number of potential victims at a low-cost and low-risk, new and readily available scamming opportunities, anonymity and concealment of identity through minimal physical contact (Blommaert & Omoniyi, 2006;Hutchings & Hayes, 2009;Ofulue, 2010;Webster & Drew, 2017). Dion (2010, p. 630) concluded that 419ers regard the Internet as an "Eldorado" In a forensic accounting context, the power of linguistic and psycholinguistics analysis techniques to understand the human behaviour reflected in fraud has been studied widely (see Nicolaides, Trafford, & Craig, 2017). Linguistic analysis techniques have been used to investigate behaviour associated with corporate fraud through study of CEO letters to shareholders, conference calls with financial analysts, and earnings press releases.…”
Section: Scamwatchmentioning
confidence: 99%